A Review of Treatment Methods and Available Therapies for Individuals with ADHD - Zuzanna Gałuszka; Natalie Papachristoforou; Daria Michałka; Monika Makar; Tomasz Bartuś; Żaneta Góra; Emilia Bąk; Justyna Głowacka; Aleksandra Kocjan; Radosław Chmiel (Quality in Sport)
This review explores treatment approaches and therapies for Attention Deficit Hyperactivity Disorder (ADHD), a neurodevelopmental condition affecting adults, with symptoms often persisting from childhood into adulthood. The research examines the efficacy, tolerability, and accessibility of pharmacological and psychosocial interventions. ADHD management necessitates a multimodal approach combining medications, behavioral therapies, and educational interventions tailored to individual needs.